Influence of preflight on the horse impact phase of a simulated yurchenko layout vault - Koh, M; Jennings, L.; Elliott, R. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Recently, key mechanical variables associated with an optimal performance of the Yurchenko layout vault for an elite female gymnast were identified [4]. The optimal vault was one that satisfied the postflight height and distance requirements stipulated by the 1997 FIG Code of Points, while maintaining a fully extended posture throughout postflight. The optimised impact technique was a combination of several factors: a greater "body angle of attack"; an increase in the vertical horse takeoff velocity of the CM; and, a larger preflight angular momentum that increased during horse impact, relative to the recorded performance. However, the individual influence of the body angle of attack or the level of preflight angular momentum on vertical horse takeoff velocity and horse impact duration is not known. The purpose of the study was therefore to investigate how selected preflight variables affects the vault performance. Methods A combined optimal control and parameter selection approach with the MISER3 optimal control software [1] was used in this study. A five-segment model (symmetry assumed), comprising the hands, upper limbs, upper trunk, lower trunk and lower limbs, was personalised with respect to the physical attributes of an elite level gymnast using the technique of [2]. Model evaluation was reported in [3]. The model was driven by joint torque histories of the wrist, shoulder, mid-trunk and hip from the optimised vault of [4]. Two separate simulations (Sim1 and Sim 2) were conducted to investigate how the initial body angle of attack or the angular momentum at impact affected the optimal vault identified by [4]. Data from the best trial reported in [4] was used as input variables. In Sim1, only the segment angular velocities were allowed to vary. In Sim2, only the initial impact configuration was allowed to vary. The simulations commenced at impact and finished at the end of postflight. Input comprised the inertial parameters, the initial segment angular coordinates and angular velocities, and the initial CM position and velocity. Model output comprised the time histories of the optimised joint torques, the segment angular orientations and velocities and the CM trajectory of the system.